INDIGENOUS KNOWLEDGE OF BUBBOR PADDAS OF SAMBAS COMMUNITY AS EDUCATIONAL VIDEO CONTENT ON BIODIVERSITY VALUE TOPIC - Adinugraha, Fajar; Grace, Mayla; Angelita B, Shezy; Kelana, Kelana (FKIP Universitas Tanjungpura, 2024)
The phenomenon of low student knowledge about the value of biodiversity can have an impact on reducing awareness of biodiversity loss. Efforts are made to study biodiversity value related to indigenous knowledge because biodiversity and indigenous knowledge have a close relationship. The indigenous knowledge of the Sambas people, known as Bubbor Paddas, has the potential to educate about biodiversity. The purpose of the research was to study Bubbor Paddas for an educational video of biodiversity. Another objective is to ascertain audience